The draft genome of watermelon (Citrullus lanatus) and resequencing of 20 diverse accessions - Guo, Shaogui; Zhang, Jianguo; Sun, Honghe; Salse, Jerome; Lucas, William J; Zhang, Haiying; Zheng, Yi; Mao, Linyong; Ren, Yi; Wang, Zhiwen; Min, Jiumeng; Guo, Xiaosen; et al. (Nature genetics, 2013)
Zhangjun Fei and colleagues report the draft genome of a Chinese elite watermelon inbred line 97103 and resequencing of 20 diverse accessions that represent the three subspecies of Citrullus lunatus . Comparative genome-wide analyses identify the extent of genetic diversity and population structure of watermelon germplasm. Watermelon, Citrullus lanatus , is an important cucurbit crop grown throughout the world. Here we report a high-quality draft genome sequence of the east Asia watermelon cultivar 97103 (2 n = 2× = 22) containing 23,440 predicted protein-coding genes. Comparative genomics analysis provided an evolutionary scenario for the origin of the 11 watermelon chromosomes derived from a 7-chromosome paleohexaploid eudicot ancestor. Resequencing of 20 watermelon accessions representing three different C. lanatus subspecies produced numerous haplotypes and identified the extent of genetic diversity and population structure of watermelon germplasm. Genomic regions that were preferentially selected during domestication were identified. Many disease-resistance genes were also found to be lost during domestication. In addition, integrative genomic and transcriptomic analyses yielded important insights into aspects of phloem-based vascular signaling in common between watermelon and cucumber and identified genes crucial to valuable fruit-quality traits, including sugar accumulation and citrulline metabolism.